1998
DOI: 10.1093/chemse/23.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Lacustrine Sockeye Salmon Return Straight to their Natal Area from Open Water Using Both Visual and Olfactory Cues

Abstract: Mechanisms of the amazing ability of salmon to migrate a long distance from open water to natal streams for spawning are still unknown. Lacustrine sockeye salmon (Oncorhynchus nerka) in Lake Toya offers an excellent model system for studying the orientation mechanism in open water, because mature fish return to the natal area with a high degree of accuracy. First we examined the percentage of fish returning to the natal area after they were released 7 km south of the natal area. Forty percent of control male m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Some of the earliest of such studies occurred on Pacific salmon in Japan and involved evaluating homing mechanisms [141] and the endocrinology of migration (reviewed in [142]). Recently, the first example of combining genomic studies with field telemetry of Pacific salmon identified the factors that are associated with migration failure in freshwater [143].…”
Section: Combining Electronic Tagging With Other Research Methodsmentioning
confidence: 99%
“…Some of the earliest of such studies occurred on Pacific salmon in Japan and involved evaluating homing mechanisms [141] and the endocrinology of migration (reviewed in [142]). Recently, the first example of combining genomic studies with field telemetry of Pacific salmon identified the factors that are associated with migration failure in freshwater [143].…”
Section: Combining Electronic Tagging With Other Research Methodsmentioning
confidence: 99%
“…In the rainbow trout, Oncorhynchus mykiss, electrophysiological and behavioural responses to magnetic fields have been demonstrated, and a magnetite-based magnetoreceptor cell has been identified in a discrete layer of the olfactory lamellae (Walker et al, 1997;Diebel et al, 2000). On the other hand, telemetric tracking of the chum salmon, Oncorhynchus keta, in the North Pacific and of sockeye salmon, Oncorhynchus nerka, in a lake in Japan indicated that these fishes do not cue to magnetic fields when homing (Yano et al, 1995;Ueda et al, 1998). Yano et al (1996) were unable to condition landlocked hime salmon, O. nerka, to imposed magnetic fields when an electric shock was used as an associated stimulus and thus concluded that hime salmon have no magnetic sense.…”
mentioning
confidence: 99%
“…It has been discussed that sensory organs other than the olfactory organ are used by salmonids when they are migrating far from the natal river. Recently, we proposed that visual cues are important for orientation during homing migration in lacustrine sockeye salmon (Ueda et al, 1998).…”
Section: Discussionmentioning
confidence: 99%